Apologies In “Whatsapp” Produced By Japanese Department Student Of Universitas Muhammadiyah Yogyakarta - Azizia Freda Savana; Rosi Rosiah (IZUMI, 2019)
(Title: Apologies In “Whatsapp” Produced By Japanese Department Student Of Universitas Muhammadiyah Yogyakarta) This paper discusses an apology in Whatsapp by Japanese Department Students of Universitas Muhammadiyah Yogyakarta in several situations use semantic formula. In era digital, Many of them always deliver their message to Whatsapp. They use Whatsapp for sharing information, expressing gratitude and apologies to their friends and teachers. Expressing apologies via Whatsapp is different from expressing it directly. Writing using Whatsapp will be more creative by using emoji or kaomoji based on the situations. Besides that, they usually abbreviate their writing on Whatsapp. The purpose of this research is to know how Japanese Department Students of Universitas Muhammadiyah Yogyakarta expressing apologize via Whatsapp in several situations to the teacher, seniors, and friends. Do they use emoji or kaomoji and how they write an apologizing with the Teacher, Seniors, and Friend? This research uses a descriptive method with qualitative approaches since analyzed descriptively with the qualitative method. The method of analysis used the semantic formula to classify apologies based on the situation. The result of this research is the student’s tendency most of them use In-speech act instruction designation (apology content, appreciation, etc.) and they not so using emoji to express apologies to teachers.   gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor